تقييم التنوع النباتي في موقع تحريج جبل النبي متى في محافظة طرطوس - قبيلي عماد; الشاطر زهير; إبراهيم عبير (Latakia University Journal -Biological Sciences Series, 2019)
تم في هذا البحث تقييم التنوع النباتي في موقع "جبل النبي متى" المشجر في سبعينات القرن الماضي بعدة أنواع حراجية و الذي يقع شرق مدينة طرطوس ضمن الطابق النبتي المتوسطي العلوي من سلسلة الجبال الساحلية الغربية، و ذلك باستخدام عدة دلائل للتنوع النباتي. أظهرت الدراسة وجود تنوع نباتي جيد في هذا الموقع المشجر بصورة عامة، كما أظهرت وجود اختلاف واضح في التنوع النباتي تبعاً للنوع الحراجي السائد و لعوامل أخرى تتعلق بشكل رئيسي بالخصائص الحراجية للمجموعة الحرجية و تتعلق بشكل أقل بطريقة تحضير الأرض للتشجير و المعاملات التربوية المطبقة، إذ ازدادت قيمة التنوع النباتي بازدياد التغطية في الطبقة الشجيرية في حين أثرت القيم الدندرومترية (المساحة القاعدية، الإنتاجية، المخزون الخشبي) سلباً في هذا التنوع. من ناحية أخرى، ترافقت طريقة التشجير في المدرجات مع تحسين في التنوع النباتي في الموقع، كما أثرت أعمال التربية الممثلة بالتفريد و التقليم بصورة إيجابية في هذا التنوع. This research aimed to evaluate the plant species diversity in Alnabe Matah Mountain in eastern Tartous, which was afforested in the seventies of the last century with many forestry species. The site belongs to the upper mediterranean vegetation zone of the western coastal mountains series. The evaluation of plant diversity was conducted through the use of several indices of plant species diversity. Generally, the study showed a good plant species diversity at this site, and a clear difference in this diversity according to dominant forestry species and other factors that are mainly related to the forest characteristics of stands, but less related to both method of land preparation for afforestation and used silvicultural treatments. Plant species diversity increased by the increase of shrub coverage; whereas dendrometry values (basal area, productivity, and wood volume) gave a negative effect on this diversity. On the other hand, the afforestation on terraces accompanied the improvement of plant species diversity. Also, the thinning and pruning works positively affected this diversity.